The Influence of Thought Patterns on Mental Health: "A Qur'anic and Scientific Perspective" - Khoirul Ibad (International Journal of Educational and Psychological Sciences, 2023)
The human mind, as the core of one's being, possesses immense power in shaping an individual's soul and mental state. If the potential of thought and emotion has often been overlooked, this study aims to delve deeply into the potency of thought in soul therapy. The research's primary objective is to formulate a comprehensive understanding of the Quranic viewpoint on thought patterns and their influence on the human psyche. This research employs a thematic interpretation method, incorporating psychological and philosophical analyses concerning Quranic concepts related to mental disturbances and their causative factors. As a result of this research, a formulated definition emerges, asserting that the term "mental disorder" arises from negative thought patterns that subsequently impact one's physical well-being. This assertion finds validation in scientific studies, which indicate that thought patterns can indeed have implications for psychological and mental health. Consequently, managing and cultivating positive thought patterns can serve as an effective therapeutic approach for individuals grappling with mental health challenges. This study bridges the realms of spirituality and science, shedding light on the profound relationship between the human mind, faith, and mental well-being.